Killing Effect and Antitoxic Activity of the Leptospira interrogans Toxin-Antitoxin System in Escherichia coli - Picardeau, Mathieu (American Society for Microbiology, 2001)
We report the first evidence of a chromosome-encoded toxin-antitoxin locus in spirochetes. This locus has been found in the pathogenic spirochete Leptospira interrogans and exhibits homologies with the pem/chp loci. The L. interrogans chp locus consists of two genes: chpK (for “killer protein”) and its upstream partner chpI (for “inhibitory protein”). Expression of ChpK in Escherichia coli results in the inhibition of bacterial growth. The coexpression of ChpI neutralizes ChpK toxicity. By Southern blot analysis, chp homologs were found in all representative pathogenic strains of L. interrogans.